A comprehensive description of sitting time in Brazilian adults: a population-based study - Sebastião, Emerson; Andrade, Flávia C. D.; Papini, Camila B.; Nakamura, Priscila M. [UNESP]; Kokubun, Eduardo [UNESP]; Gobbi, Sebastião [UNESP] (Springer Nature, 2019)
Aim: There is limited data from population-based studies addressing sedentary behavior in developing countries such as Brazil. This study provides a comprehensive description of sitting time in adults living in a mid-size city in Brazil. Subjects and methods: Trained interviewers used the International Physical Activity Questionnaire to assess sitting time information. Logistic regression was used to examine the association between the independent variables with sitting time. The study had 1008 participants. Results: The median sitting time value for weekdays was 180 min (interquartile range: 120–300) and 240 minutes (interquartile range: 120–360) for weekend days. Individuals between 30 and 69 years of age and those of lower socioeconomic status are less likely to sit for more than 180 min during the weekdays compared to their younger and wealthier counterparts respectively. Individuals with higher educational levels and those with pain had higher levels of sitting time during the weekend. Disability was associated with greater sitting time during both week and weekend days. Conclusion: Participants in our study reported a median sitting time of 3 and 4 h for week and weekend days respectively. We further observed an association between sitting time and age, socioeconomic status, educational attainment, and disability. Identifying groups at higher levels of sitting time is critical for devising initiatives aiming to reduce time spent in sedentary behavior, increase physical activity, and improve health.
Keywords: Disease prevention; Health promotion; Motor activity; Sedentary behavior